2019
DOI: 10.1096/fj.201802281r
|View full text |Cite
|
Sign up to set email alerts
|

Distinct expression pattern of periostin splice variants in chondrocytes and ligament progenitor cells

Abstract: Periostin (POSTN), a secretory matricellular matrix protein, plays a multitude of biologic functions. Various splice variants of POSTN have been described; however, their expression pattern and functional implications are not completely understood. This study was undertaken to decipher the differential expression pattern of POSTN and its splice variants in various tissues and cell types. We show that POSTN was more highly expressed in anterior cruciate ligament (ACL) remnants compared with articular cartilage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 56 publications
4
33
0
Order By: Relevance
“…Third, periostin-DDR1 interaction results in AKT activation and increased β-catenin levels. We have previously reported that Postn activates Wnt/β-catenin signaling, and the Wnt signaling inhibitor CCT031374 hydrobromide, which blocks β-catenin stabilization and thus inhibits TCF-dependent transcription, abrogates Postn induction of MMP-13 expression in human chondrocytes [29]. In the present study, the DDR1 inhibitor 7rh also blocked Postn-induced MMP-13 upregulation, as well as AKT phosphorylation and β-catenin stabilization.…”
Section: Plos Onesupporting
confidence: 69%
See 1 more Smart Citation
“…Third, periostin-DDR1 interaction results in AKT activation and increased β-catenin levels. We have previously reported that Postn activates Wnt/β-catenin signaling, and the Wnt signaling inhibitor CCT031374 hydrobromide, which blocks β-catenin stabilization and thus inhibits TCF-dependent transcription, abrogates Postn induction of MMP-13 expression in human chondrocytes [29]. In the present study, the DDR1 inhibitor 7rh also blocked Postn-induced MMP-13 upregulation, as well as AKT phosphorylation and β-catenin stabilization.…”
Section: Plos Onesupporting
confidence: 69%
“…Postn has the unique property of stimulating catabolic effects in cartilage while promoting osteogenesis in bone. Postn is produced by multiple joint tissues, including bone, cartilage, ligaments, meniscus, and synovium under normal or injury-induced conditions [29]. Karlsson et al and two other groups have independently shown increased expression of Postn in cartilage and subchondral bone of human OA-affected joints [3,4,[32][33][34]; and elevated levels of Postn have also been reported in human OA synovial fluids, as well as in synovial fluids of anterior cruciate ligament injury patients [35][36][37].…”
Section: Plos Onementioning
confidence: 99%
“…ACL remnants were removed from patients undergoing ACL reconstruction surgery. ACL progenitor cells that have been shown to express stem cell markers 30,31 were isolated as described before 32 . Moreover, we also isolated ACL fibroblasts as described previously 31 with slight modifications.…”
Section: Acl Sampling and Cell Preparationmentioning
confidence: 99%
“…Originally, it was termed osteoblast-specific factor 2 (OSF-2) due to its localization in proximity to the periodontal ligament and periosteum of mice; it was renamed periostin in 1999 and subsequently classified as a matricellular protein in 2007 by Norris and Colleagues [ 18 ]. Structurally, periostin is a secreted 90 kDa N terminus-glycosylated protein with a multi-domain structure, including amino-terminal EMI domain, four tandem fascilin domains, and a carboxyl-terminal domain [ 19 ], with several different isoforms described [ 20 , 21 , 22 , 23 ]. This complex domain structure allows for numerous interactions with extracellular/secretory proteins [ 24 ], via which exerts its multiple functions.…”
Section: Gla-containing Ecm Proteinsmentioning
confidence: 99%